1976
DOI: 10.1210/jcem-42-5-804
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Plasma Glucagon Immunoreactivity in a Patient with Suspected Glucagonoma

Abstract: Gel filtration of plasma from a patient with a clinical syndrome of glucagonoma and a total plasma glucagon level of 2600 pg/ml, revealed the four glucagon immunoreactive fractions found in normal subjects. The total hyperglucagonemia observed was due to high levels of true glucagon and proglucagon moieties. The so-called "big plasma glucagon" (BPG) measured 190 pg/ml (normal average 113 +/- 79 pg/ml, Mean +/- SD, N = 10); the large glucagon immunoreactivity, LGI (9000 mol wt), measured 625 pg/ml (normal aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…In several subsequent reports, it was confirmed that the high concentrations measured in these patients were frequently due to immunoreactive components of larger molecular size than glucagon [5,[12][13][14][15][16][17][18][19] in addition to glucagon-sized components.…”
Section: Discussionmentioning
confidence: 76%
“…In several subsequent reports, it was confirmed that the high concentrations measured in these patients were frequently due to immunoreactive components of larger molecular size than glucagon [5,[12][13][14][15][16][17][18][19] in addition to glucagon-sized components.…”
Section: Discussionmentioning
confidence: 76%
“…Patients with glucagonomas frequently have a severe skin rash and carbohydrate intolerance (23,24); none of' the affected family members had dermatitis and all had normal glucose tolerance tests. Although excessive levels of large molecular weight IRG have been reported in glucagonoma patients, these patients also had excessive levels of 3,500-dalton IRG (25,26). The levels of S-IRG, which represenit predominanitly 3,500 IRG, were normal in each of our subjects (Fig.…”
Section: Resultsmentioning
confidence: 43%
“…In marked contrast, O'Connor and Lazarus found no precursor-product relationship between 9,000-and 3,500-daltoin glucagoni in pigeon islets (21). In addition to 3,500-dalton IRG, humani plasnma contains variable amounts of 160,000-and 9,000-dalton IRG, with elevated levels of the latter being common in patients with chroniic renal failure (8,22) and in those with glucagononmas (23)(24)(25)(26). Studies with human islets have demonstrated the inicorporation of [3H]tryptophan into both 9,000-and 3,500-dalton IRG (10).…”
Section: Resultsmentioning
confidence: 95%
“…Glucagon immunoreactivity is heterogeneous in human plasma [11,12,26]. In addition to glucagon, plasma of normal subjects and of patients with glucagonoma contains proglucagon [6,7,11,12,19,24,25,28,29], a 9000-dalton protein devoid of glucagon bioactivity [20] formerly termed "large" glucagon immunoreactivity, and preproglucagon (a 180 amino acid protein) [12,24,25,28] previously referred to as "big" plasma glucagon, which all cross-react with the anti-glucagon antibody K30 [27,29] specific for the carboxyl-terminal region of glucagon [2]. In the present study determination of IRG in plasma subjected to gel chromatography clearly revealed three distinct immunoreactive glucagon species in the molecular weight range of 3500, 9000, and larger than 13 000 daltons, resembling glucagon, preglucagon, and preproglucagon, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples were placed on polyacrylamide gel (Bio-Gel P-30, Bio-Rad Laboratories, Richmond, CA, USA), column size 1 x 50 cm, and eluted with 0.2 mol/1 glycine (Sigma Diagnostics, St. Louis, MO, USA) containing 0.25% human serum albumin (Sigma Diagnostics), 500 U aprotinin/1, and 1% normal sheep serum, pH 8.8, at 4°C [7,24,25]. The flow rate was 5 ml/h.…”
Section: Methodsmentioning
confidence: 99%